Comparison of design and implementation of hybrid systems in prototype vehicles - McKenney, Benjamin, author; Quinn, Jason, advisor; Bradley, Thomas, committee member; Windom, Bret, committee member (Colorado State University. Libraries, 2021)
With the continual increased concern with vehicle emissions, the automotive industry is focused on the advancement of new technology to reduce fuel consumption and curb emissions. The Colorado State University (CSU) Vehicle Innovation Team (VIT) has recently constructed two separate vehicle prototypes that utilize state of the art automotive technology for the purpose of furthering automotive research, specifically in the area of new controls techniques. The focus of these two projects have been on the integration of hybrid powertrains into traditional combustion engine driven vehicles. The vision, scope, and overall goals of each research project vary drastically, and thus the design choices vary as well. The contents of this paper will focus on the two separate hybrid vehicle projects and seek to capture the design and integration decisions that were made and provide insight and reasoning as to why the choices were made. This process first begins with the background and scope of each project, which lays the groundwork for the design requirements that will drive each of the vehicle's overall architecture, design, function, and performance. Once these design requirements are understood, the component selection process is then examined for each vehicle. Fabrication and integration of the hybrid powertrain within the vehicle is also explored in a similar manner, in which the techniques and methodologies give an insight into the prototyping process. Throughout the sections the two different vehicle projects will be compared to one another and the differences are discussed in detail as it pertains to the design requirements of each project. Finally, the testing procedures as well as results from the hybrid systems are presented.
Keywords: hybrid vehicle; battery; prototypes